Hyperactive Repeating Fast Radio Bursts from Rotation-modulated Starquakes on Magnetars - Jia-Wei Luo; Jia-Rui Niu; Wei-Yang Wang; Yong-Kun Zhang; De-Jiang Zhou; Heng Xu; Pei Wang; Chen-Hui Niu; Zhen-Hui Zhang; Shuai Zhang; Ce Cai; Jin-Lin Han; et al. (The Astrophysical Journal, 2025)
The nondetection of periodicity related to rotation challenges magnetar models for fast radio bursts (FRBs) with FRB emission from close to the magnetar surface. Moreover, a bimodal distribution of the burst waiting times is widely observed in hyperactive FRBs, a significant deviation from the exponential distribution expected from stationary Poisson processes. By combining the epidemic-type aftershock sequence earthquake model and the rotating vector model involving the rotation of the magnetar and orientations of the spin and magnetic axes, we find that starquake events modulated by the rotation of FRB-emitting magnetar can explain the bimodal distribution of FRB waiting times, as well as the nondetection of periodicity in hyperactive repeating FRBs. We analyze data from multiple FRB sources, demonstrating that differences in waiting time distributions, and to some extent, observed energies can be explained by varying parameters related to geometric properties of the magnetar FRB emission and starquake dynamics. Our results show that the assumption that all FRBs are repeaters is compatible with our model. Notably, we find that hyperactive repeaters tend to have small magnetic inclination angles in order to hide their periodicity. We also show that our model can reproduce the waiting time distribution of a pulsar phase of the galactic magnetar SGR J1935+2154 with a larger inclination angle than the hyperactive repeaters, which could explain the detection of spin period and the relatively low observed energy for FRBs from the magnetar. The spin periods of hyperactive repeaters are not well constrained, but most likely fall in the valley region between the two peaks of the waiting time distributions.